ANALISIS MODEL TAHANAN DEFORMASI EKSPERIMENTAL PADA PENGEROLAN DINGIN PADUAN KUNINGAN CARTRIDGE - Qamaruddin, Qamaruddin (JURNAL ILMIAH TEKNIK MESIN, 2015)
A model of resistance to deformation as a result of cold rolling process of Cartridge Brass alloy conducted atlaboratory, was obtained. Based on this experimental model, to be able to apply the theoritical models to meetthe scale level of laboratory, they were modified. The regression of experiment results and the modifiedtheoritical models are reasonably able to predict the resistance to deformation. The models of resistance todeformation both experimental and modified ones show the average deviation of about 10%Keywords: Cold Rolling, Resistance to deformation, Brass alloy